2017
DOI: 10.1016/j.taap.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug and toxin extrusion proteins mediate cellular transport of cadmium

Abstract: Cadmium (Cd) is an environmentally prevalent toxicant posing increasing risk to human health worldwide. As compared to the extensive research in Cd tissue accumulation, little was known about the elimination of Cd, particularly its toxic form, Cd ion (Cd2+). In this study, we aimed to examine whether Cd2+ is a substrate of multidrug and toxin extrusion proteins (MATEs) that are important in renal xenobiotic elimination. HEK-293 cells overexpressing the human MATE1 (HEK-hMATE1), human MATE2-K (HEK-hMATE2-K) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Our recent findings and those from others have indicated that OCT2 and MATEs are Cd ion transporters. [20][21][22] However, given their moderate affinity toward Cd ions, they are probably not the primary transport mechanisms for Cd. Other mechanisms or transporters, such as the receptor-mediated endocytosis of the Cd 2þ -protein complex, calcium channels, zinc transporters, transient receptor potential channels, divalent metal-ion transporters, amino acid/cystine transporters, and the adenosine triphosphatase multidrug resistance protein 1 (MDR1), have been implicated in transporting Cd across the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent findings and those from others have indicated that OCT2 and MATEs are Cd ion transporters. [20][21][22] However, given their moderate affinity toward Cd ions, they are probably not the primary transport mechanisms for Cd. Other mechanisms or transporters, such as the receptor-mediated endocytosis of the Cd 2þ -protein complex, calcium channels, zinc transporters, transient receptor potential channels, divalent metal-ion transporters, amino acid/cystine transporters, and the adenosine triphosphatase multidrug resistance protein 1 (MDR1), have been implicated in transporting Cd across the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Cd has been reported to be a moderate substrate of OCTs 20,21 and MATEs. 22 Our initial intention was to examine the potential of Cd to inhibit OCT/MATE-mediated drug disposition. With stable human embryonic kidney (HEK)293 cells expressing human OCT2 (HEK-human(h)OCT2), we unexpectedly found that Cd pretreatment could increase the activities of human (h) OCT2 in a time-and concentrationdependent manner (Figure 1a; Supplementary Figure S1A).…”
Section: Exposure Increased Oct2 Activity and Its Membrane Expressionmentioning
confidence: 99%
“…In Arabidopsis, the MATE-related transporter DETOXIFICATION 1 (AtDTX1) has been described as an efflux transporter that detoxifies plant-derived or exogenous toxic compounds including Cd from the cytoplasm [ 63 ]. Interestingly, a recent study on mammalian MATEs has provided the first evidence that MATE transporters are involved in the cellular transport and detoxification of Cd [ 64 ]. Therefore, it would be worth investigating the role of the Cd-induced plant MATE transporters in combating Cd toxicity in planta .…”
Section: Discussionmentioning
confidence: 99%
“…Computational modeling suggests that As binds to free thiols on the MT molecule [79,80], which may reduce the oxidative injury induced by exposure to As [81]. Interestingly, it has been suggested that the formation of MT-As complexes does not occur following acute exposure to iAs; rather, it was postulated that these complexes are formed only in cases of chronic exposure [82].…”
Section: Environmentally Relevant Toxic Metalsmentioning
confidence: 99%